Hethitica VII - Jucquois, G.; Duhoux, Y.; Neu, E.; Laroche, E. (1987)
Bibliothèque des Cahiers de l'Institut de Linguistique de Louvain, 36. Comité de Rédaction: E.Laroche - E. Neu - Y. Duhoux -G. Jucquois - R. Lebrun